The mechanisms of milder clinical symptoms of COVID-19 in children compared to adults - Caiyin Luo; Wanwen Chen; Junying Cai; Yuwen He (BMC, 2024)
Abstract In stark contrast to adult patients, children who contract Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) typically manifest milder symptoms or remain asymptomatic. However, the precise underlying mechanisms of this pathogenesis remain elusive. In this review, we primarily retrospect the clinical characteristics of SARS-CoV-2 infection in children, and explore the factors that may contribute to the typically milder clinical presentation in pediatric Coronavirus Disease 2019 (COVID-19) patients compare with adults patients with COVID-19. The pathophysiological mechanisms that mitigate lung injury in children are as follows: the expression level of ACE2 receptor in children is lower; the binding affinity between ACE2 receptors and viral spike proteins in children was weaker; children have strong pre-activated innate immune response and appropriate adaptive immune response; children have more natural lymphocytes; children with COVID-19 can produce higher levels of IgM, IgG and interferon; children infected with SARS-CoV-2 can produce lower levels of IL-6 and IL-10; children have fewer underlying diseases and the lower risk of worsening COVID-19; children are usually exposed to other respiratory viruses and have an enhanced cross-reactive immunity. Comprehending the relative contributions of these processes to the protective phenotype in the developing lungs can help in the diagnosis, treatment and research pertaining to children with COVID-19.